ПРЕКРШОЦИТЕ ПРОТИВ ЈАВНИОТ РЕД И МИР ВО РЕПУБЛИКА МАКЕДОНИЈА: ТЕОРЕТСКИ И ПРАКТИЧНИ АСПЕКТИ - Gruevska Drakulevski, Aleksandra (MACEDONIAN JOURNAL FOR CRIMINAL LAW AND CRIMINOLOGY, 2016)
The paper analyses the theoretical and practical aspects of misdemeanors against the public order in the country. The interest of the Law on Misdemeanors Against the Public Orderis determined by the mass execution of misdemeanors against the public order, suggesting a degree of social and public (in)discipline, (non)compliance with the legal system, the way of functioning of the society and the attitude of citizens towards the authorities. From the analysis of the misdemeanors against the public order in the period 2001- 2013, the author concludes that most perpetrated misdemeanors against the public order are assault in a public place, participation, causing or inciting a brawl etc., which clearly indicates low culture of citizens, therefore, solving problems by force, violence, aggression, insult, humiliation, intolerance, disrespect of the common life, endangering the safety of others, creating uncertainty, revealing the socio-pathological phenomena ofdisrespect of officials, disrupting their work etc. Also, the paper analysed court judgments for misdemeanors against the public order. The general conclusion is that there is a disparity in the imposed penalties for the same offense in different courts. Furthermore, the author emphasizes the necessity of revising the provision of the Law on Misdemeanors which leaves an opportunity in the special laws to provide fines with greater height than that provided by the Law on misdemeanors as a general law which dilutes the meaning of punishment from one hand, and the essence of misdemeanor responsibility, on the other. Namely, the author again emphasizes the primarily preventive function of the Law on Misdemeanors and the on Misdemeanors against the Public Order.
THE MISDEMEANORS AGAINST THE PUBLIC ORDER IN THE REPUBLIC OF MACEDONIA: THEORETICAL AND PRACTICAL ASPECTS
Keywords: Misdemeanors, Misdemeanors against the Public Order, Sanctions, Fines, Law on Misdemeanors, Law on Misdemeanors against the Public Order; прекршоци,прекршок против јавен ред и мир, прекршочни санкции, глоба, Закон за прекршоците, Закон за прекршоците против јавниот ред и мир.